The Role of Mass Media in representation of a “Black-and-white” Discourse of the World View - Anastasia Mikhailovna Kovaleva (Управленческое консультирование)
This article focuses on the media participation in the racism reproduction process and construction of bipolar «black-white» reality. There are problems in Russia and other countries like USA with two main kinds of racism: straight and institutionalized, deeply rooting that based on fear, prejudices and feeling of racial superiority. Media treat some events in racism discourse way of thinking purposefully. Publications accentuate public attention on ethnicity of conflict participants which apply to ethnic minority groups and characterize them only as threatening and deviant persons. When media make this, an impression will arise that this deviance exists independently from economical, political, social problems. Review of Ferguson’s and Manejnaya square’s riots demonstrates that each side of conflict think that all guilty lay on its opposite side and media totally represent this point of view. Social reality is objective, but media form their own reality that reflect someone’s interests, for example, interests of parties, lobbies, individuals, groups and so on. Racism permeates all our social pores. Currently «racism without racists» is a special thorn in our society’s body and it implies an indirect discrimination, for instance, employer can find many legally justifie d reasons for not to hire a member of certain nationality.